Implementasi Good Hospital Governance di Rumah Sakit Prima Husada Cipta Medan - Kiki Riztya Wibowo; Nur aini .; Mappeaty Nyorong (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
Good Hospital Governance is a governance system in implementing good management and can assist in efforts to improve company performance and service quality, especially hospital companies that provide health services to the community. improve service and management innovation. The purpose of this study is to determine and analyze the implementation of aspects of Good Hospital Governance such as aspects of transparency, accountability, responsibility, independence, fairness and obstacles faced, this research is a qualitative study that aims to prove the phenomena in research problems. Research informants as many as 7 people including the board of commissioners, director, head of finance, sdm, a quality committee, head of nursing and nurses. The results showed that the implementation of Good Hospital Governance at the Prima Husada Cipta hospital Medan on the transparency aspect had been running but had not been carried out as a whole because many aspects were hospital privacy, in the implementation of hospital accountability it had been carried out in accordance with applicable regulations and standards. the implementation of the responsibility aspect that the hospital has carried out such as health human resources that have carried out their duties and functions in accordance with their respective professions, on the independence aspect that the hospital can carry out everything independently, in the aspect of fairness that the hospital has implemented and treated all employees fairly and fair.Suggestions in this study are that it is necessary to implement aspects of transparency, accountability, responsibility, independence and fairness that can be carried out better and overall and can be used as targets in the internal audit of Prima Husada Cipta Hospital Medan